The Effect of Alcohol and Sexual Arousal on Explicit and Implicit Condom Attitudes and Intentions to Use a Condom - Wolfs, Kenny; Bos, Arjan E. R.; Mevissen, Fraukje E. F.; van Lankveld, Jacques J. D. M. (Archives of sexual behavior, 2023)
Alcohol and sexual arousal are contextual determinants of condomless sex. Dual-process theory postulates that two types of cognitive processing contribute to the regulation of behavior: one that is fast, intuitive and automatic, and another that is slower and deliberative. This study applied a dual-process model to investigate condomless sexual behavior, highlighting the potential importance of implicit attitudes in condomless sex. We investigated whether the impact of alcohol and sexual arousal on condom use-related attitudes and intentions was explained by diminished working memory capacity, as dual-process models suggest. We also investigated whether this effect could be explained by implicit and explicit attitudes toward condom use. Male participants ( N = 30) were randomized using a 2 × 2 within-subjects design that manipulated alcohol intoxication (placebo vs. alcohol beverages) and sexual arousal (neutral vs. erotic movie clips). We measured participants’ working memory capacity, intentions to use a condom, and explicit and implicit attitudes toward condom use. Significant main effects of alcohol intoxication and sexual arousal on working memory capacity were found. No significant interaction was found for the combined effect of alcohol intoxication and sexual arousal on intentions to use a condom. There was no significant effect of implicit attitudes on intentions to use a condom, although a trend toward significance ( p = 0.06) was found for the effect of implicit attitudes on intentions to use a condom when participants were in a state of alcohol intoxication. Theoretical and practical implications of this study are discussed.